Dampak Politik Anggaran Pendidikan terhadap Penghentian Beasiswa: Studi Kasus SMAN Bali Mandara - Darmawan, I Made Dwi Hita; Ratmayanti, Nyoman Gita Saraswati (Ministry of Home Affairs, 2023)
The issue of politicization in the education sector has garnered significant attention in everyday discourse, yet its exploration in academia remains limited. Often, government policies fail to align with public expectations. This study delved into the public debate surrounding the abrupt discontinuation of the scholarship program at SMAN Bali Mandara by the government, seeking to investigate the underlying reasons. The rationale behind the government's decision to discontinue scholarships, while allocating substantial funds to other sectors, remained unclear, as did the subsequent impact of the discontinuation. Consequently, the public and education activists demanded clarification from the government. This study aimed to examine the politicization of the education budget by analyzing the APBD report and public responses. Rather than providing scholarships, the government prioritized the construction of new school infrastructure in various regions. This study employed a qualitative approach with a literature review method. The author collected data from APBD reports, BPS data, online mass media, scientific articles, and other sources to support an in-depth analysis. The study encompassed problem identification, literature review, determination of the study's purpose and objectives, data collection, data analysis, interpretation, and reporting of results. The study revealed that the government abruptly and unilaterally discontinued the scholarships at SMAN Bali Mandara. The government justified this action by claiming it aimed to equalize all schools. Under the pretext that all schools should admit underprivileged students, not just SMAN Bali Mandara, the government concentrated its efforts on constructing 14 new schools. However, based on the analyzed data, this study found that this policy was neither effective nor efficient.